Novel docetaxel-loaded nanoparticles based on PCL-Tween 80 copolymer for cancer treatment - Mei L (Dove Medical Press, 2011)
Yuandong Ma1,2*, Yi Zheng1,2*, Xiaowei Zeng1-3*, Liqin Jiang4, Hongbo Chen1,2, Ranyi Liu5, Laiqiang Huang1,2, Lin Mei1,21School of Life Sciences, Tsinghua University, Beijing, 2Division of Life and Health Sciences, Graduate School at Shenzhen, Tsinghua University, Shenzhen, Guangdong, 3Materials and Environment Experimental Center, Department of Materials Science and Engineering, Qinhuangdao Branch, Northeastern University, Qinhuangdao, 4Insitute of Biomedical Engineering, Peking Union Medical College, Chinese Academy of Medical Sciences, Tianjin, 5State Key Laboratory of Oncology in South China, Sun Yat-sen University Cancer Center, Guangzhou, People’s Republic of China *These authors contributed equally to this workBackground: The formulation of docetaxel available for clinical use (Taxotere®) contains a high concentration of polysorbate 80 (Tween 80). After incorporation of Tween 80 into poly-ε-caprolactone (PCL)-Tween 80 copolymer, the relative amount of Tween 80 should be decreased and the advantages of PCL and Tween 80 should be combined.Methods: A novel PCL-Tween 80 copolymer was synthesized from ε-caprolactone and Tween 80 in the presence of stannous octoate as a catalyst via ring opening polymerization. Two types of nanoparticle formulation were made from commercial PCL and a self-synthesized PCL-Tween 80 copolymer using a modified solvent extraction/evaporation method.Results: The nanoparticles were found by field emission scanning electron microscopy to have a spherical shape and be 200 nm in diameter. The copolymers could encapsulate 10% of the drug in the nanoparticles and release 34.9% of the encapsulated drug over 28 days. PCL-Tween 80 nanoparticles could be internalized into the cells and had higher cellular uptake than the PCL nanoparticles. The drug-loaded PCL-Tween 80 nanoparticles showed better in vitro cytotoxicity towards C6 cancer cells than commercial Taxotere at the same drug concentration.Conclusion: Nanoparticles using PCL-Tween 80 copolymer as drug delivery vehicles may have a promising outcome for cancer patients.Keywords: cancer chemotherapy, docetaxel, nanoparticles, PCL-Tween 80